Pembelajaran Jarak Jauh dalam Pembelajaran Pendidikan Agama Islam - Amaliah, Nur; Usman, Syahruddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
This article explores the implementation of distance learning in Islamic Religious Education (PAI) during the digital era. Distance Learning (DL) emerged as a primary educational alternative during the COVID-19 pandemic, revealing both benefits and challenges in fostering spiritual values. Advantages of DL include flexibility in time and location, expanded access to Islamic materials via digital platforms, and the opportunity to integrate religious values with technology through tools such as Qur’an apps and automatic prayer time reminders. However, DL faces obstacles including limited teacher-student interaction for character building, internet and device limitations, and declining student motivation due to unconducive home learning environments. Solutions involve active collaboration between teachers and parents as spiritual companions, and the use of creative teaching methods such as interactive quizzes, short dakwah videos, and Islamic storytelling. Platforms like Google Classroom, Zoom, and WhatsApp Group can also be optimized to maintain engagement and ensure the effectiveness of Islamic learning remotely